Regional groundwater flow and accumulation of a massive evaporite deposit at the margin of the Chilean Altiplano - Lilly G. Corenthal; David F. Boutt; Scott A. Hynek; Lee Ann Munk (Geophysical Research Letters)
Abstract Focused groundwater discharge in closed basins provides opportunities to investigate mechanisms for closing hydrologic and solute budgets in arid regions. The Salar de Atacama (SdA), adjacent to the Central Andean Plateau in the hyperarid Atacama Desert, provides an extreme example of halite (>1800 km3) and lithium brine (~5000 ppm) accumulation spanning late Miocene to present. Minimum long‐term water discharge needed to sustain halite accumulation over this timescale at SdA is 9–20 times greater than modern recharge (and double wet‐climate paleorecharge) within the topographic watershed. Closing this imbalance requires sourcing water from recharge on the orogenic plateau in an area over 4 times larger than the topographic watershed. Prolonged water discharge at SdA requires long residence times, deep water tables in recharge zones coupled with persistent near‐surface water tables in discharge areas, and large contributing areas characterized by strong gradients in landscape and climate resulting from plateau uplift.